Acerca de las téseras de hospitalidad latinas de la Península Ibérica (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this paper the latin tesserae hospitalitatis caracteristics from the republican age found in the Iberic Peninsula are revised, and it is presented the possibility that all of them correspond to indigenous agreements similars to the ones consignated at the celtiberic tesserae, with the exception of one tessera discovered in Teruel that it may be the only exemple of interindividual hospitality agreement in a similar way to the well known in Italy.